CLEANED Environment Assessment of small ruminant production systems in Ethiopia: Baseline Validation Workshop Report. - Ashagrie, Aemiro Kehaliew; Beraedo, Worku Bedeke; Mukiri, Jessica; Getachew, Tesfaye; Tigabie, Abiro; Haile, Aynalem; Mekonnen, Mesfin; Rischkowsky, Barbara A.; Notenbaert, An Maria Omer (Bioversity International and the International Center for Tropical Agriculture, 2021)
The SmaRT pack project is the implementation of integrated approaches of small ruminant production and productivity improvement technologies of breeds through community-based breeding improvement, feed & nutrition, animal health, collective marketing, and environmental sustainability in Ethiopia. Part of the Livestock CRP operating in Menz,Bonga, Abergela and Doyogena. In the framework of this project, the Alliance of Biodiversity International and the International Center for Tropical Agriculture (CIAT) and the International Center for Agriculture Research in the Dry Areas, (ICARDA), together with their partners, are jointly working on Comprehensive Livestock Environmental Assessment for Improved Nutrition, a Secured Environment and Sustainable Development (CLEANED) of the Small Ruminant value chain, in Menz, Bonga, Doyogena and Abergele, in Ethiopia. This report presents the discussions and outputs of the virtual CLEANED internal expert validation workshop that took place on Teams 25th June 2021. Due to the political unrest and COVID-19 situation in Ethiopia, this was an internal validation workshop. Together with experts from CIAT, the International Livestock Research Institute (ILRI) and ICARDA.The workshop aimed to validate the environmental impacts quantified by CLEANED for small ruminant systems in Ethiopia. CLEANED runs were carried out for Menz, Bonga, Doyogena and Abergele with key input data including farm inputs, herd composition and animal whereabouts. Based on these data, the model quantifies land use and water requirements, nutrient balances and greenhouse gas emissions (GHGe). This is a first step in understanding environmental trade-offs in the modeled systems and forms the basis for designing systems with a reduced environmental footprint and that enhance ecosystem services.